Where are they from? Pre-service educators' views on place and professional identity. Issue 1 (2nd January 2021) - Smith, Dorothy; Weller, Jacolyn; Starks, Donna; Kamara, Martha
ABSTRACT: Australian pre-service teachers (PSTs) increasingly find themselves in classrooms where students have a diversity of backgrounds, which can lead to questions about the PST's own place identity and how much of this identity they should disclose to students. This article explores how seven PSTs engage with their own sense of place identity when responding to the prompt: "What do you say when people ask you where you are from?" The findings bring to the fore absences of critical reflection from PSTs about the importance of their own place identity, a reluctance to talk about PST place identity in school contexts, and tensions created by a mismatch between PST place identity and professional identity. The cases presented in this article provide a starting point for opening discussions about the intersections between place identity and professional identity.